Posar como marginal (Altre Modernità, 2019)
This work proposes that the Brazilian writer Ferréz and his characters should be seen as poseur. To reflect on the pose of the marginal, this work uses the proposal of Sylvia Molloy in her book Poses de fin de siglo, where Molloy, among other things, argues that the authors use the bodies to represent cultural statements and testimonies. The main analysis of this work will be based on the first two novels by Ferréz, Capão Pecado (2002) and Manual Prático do Ódio (2003). Likewise, this work proposes that posing is a much more appropriate tactic as a project to negotiate, claim and articulate an individual or collective identity for those who are marginalized. This work examines the poses to better understand the marginal’s world. In the work it will be shown how the characters of the Literatura Marginal of Ferréz talk mostly through their appearance, dress, gestures. The body of the marginal will be understood as a visible manifestation of self-government.